2012
DOI: 10.2527/jas.2011-4572
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGY AND ENDOCRINOLOGY SYMPOSIUM: Harnessing basic knowledge of factors controlling puberty to improve synchronization of estrus and fertility in heifers1

Abstract: The development of replacement heifers is a major economic investment for all beef and dairy operations. The costs associated with heifer development cannot be recovered if heifers do not conceive and remain productive in the herd; therefore, heifers need to conceive early in the breeding season or risk being culled. Previous research has reported up to a 21% increase in fertility from pubertal estrus to the third estrus of a heifer. The use of reproductive tract scores to determine pubertal status has demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 135 publications
1
32
0
6
Order By: Relevance
“…This finally triggers the switch to a positive feedback of oestradiol driving an LH surge (Day et al, 1987). A heifer reaches puberty when she ovulates a potentially fertile oocyte and some definitions also stipulate that this should be accompanied by visual signs of oestrus (Perry, 2012). In practice the two events of first oestrus and first ovulation are often separated.…”
Section: Timing Of Pubertymentioning
confidence: 99%
“…This finally triggers the switch to a positive feedback of oestradiol driving an LH surge (Day et al, 1987). A heifer reaches puberty when she ovulates a potentially fertile oocyte and some definitions also stipulate that this should be accompanied by visual signs of oestrus (Perry, 2012). In practice the two events of first oestrus and first ovulation are often separated.…”
Section: Timing Of Pubertymentioning
confidence: 99%
“…In agreement, Perry et al (1991) observed that the conception rate of heifers bred at the first observed post-pubertal oestrus was 36 percentage points lowered than their counterparts bred at later oestrus events. Thus, the timing of puberty and the proportion of heifers that are pubertal before the planned onset of their first breeding season is critically important to overall herd reproductive efficiency (Perry, 2012).…”
Section: Occurrence and Timing Of Puberty In Replacement Heifersmentioning
confidence: 99%
“…Despite this it is clear that differences exist between breeds and breed types values of 60% typical for European-derived beef breeds, 55% for dual purpose beef/dairy breeds and 65% for Bos indicus cattle (Larson, 2007). Traditionally the recommended target weights for beef heifers at puberty (pre-breeding) was 0.60 to 0.65 (Whittier et al, 2005;Engelken, 2008), and at first breeding, 0.65 to 0.70 (Whittier et al, 2005;Perry, 2012) of estimated mature weight. These target weights, though frequently challenging to attain in practice, ensure that a very high proportion of heifers are post-pubertal at the onset of the breeding season, can easily attain 85% of mature weight at time of first calving and are sufficiently physically well developed to minimise dystocia, thus facilitating earlier recommencement of cyclicity post-calving and successful rebreeding.…”
Section: Occurrence and Timing Of Puberty In Replacement Heifersmentioning
confidence: 99%
See 1 more Smart Citation
“…The average heifer weight at yearling suggests that the main limitation for breeding yearling is body weight at the start of the breeding season (Bolze and Corah, 1993;Perry, 2012). The age of first mating in beef cattle is an important event that has an economic impact on the production system efficiency (Hugh et al, 2011;Laske et al, 2012).…”
Section: Introductionmentioning
confidence: 99%